Teachers and the interactive whiteboards - Biró, Piroska (Teaching Mathematics and Computer Science, 2012)
The spread of IWB (Interactive WhiteBoard) around the world changes, reforms and modernizes the traditional teaching methods. We can find these new ICT devices in more and more schools in Hungary as well and the use of it is getting widespread in everyday teaching. The teachers have the greatest role in the proper use of IWB during the lessons and they are also responsible for providing students with creative and motivating tasks lesson by lesson. In the following research, the advantages of the IWB are highlighted, the difficulties of its usage and the teachers' attitude towards the new ICT devices by asking 205 teachers from different primary and secondary schools. The results are mainly based on questionnaires.